2005
DOI: 10.1088/0031-9155/50/24/013
|View full text |Cite
|
Sign up to set email alerts
|

Method for determination of the mean fraction of glandular tissue in individual female breasts using mammography

Abstract: The nationwide breast cancer screening programme using mammography has been in full operation in the Netherlands since 1997. Quality control of the screening programme has been assigned to the National Expert and Training Centre for Breast Cancer Screening. Limits are set to the mean glandular dose and the centre monitors these for all facilities engaged in the screening programme. This procedure is restricted to the determination of the entrance dose on a 5 cm thick polymethylmethacrylate (PMMA) phantom. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 12 publications
0
17
1
Order By: Relevance
“…A method was used to derive glandularity of the individual compressed breasts using mammography by comparing measured attenuation in the actual compressed female breast during mammography and calculated attenuation in a breast model as a function of compressed breast thickness, glandularity and radiation quality (Jansen et al 2005).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A method was used to derive glandularity of the individual compressed breasts using mammography by comparing measured attenuation in the actual compressed female breast during mammography and calculated attenuation in a breast model as a function of compressed breast thickness, glandularity and radiation quality (Jansen et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The outer part of the compressed breast model is modelled using a 5 mm thick layer of adipose tissue. The overall breast thickness is varied and values of 11-110 mm have been used (Jansen et al 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, SHI et al 21) reported breast skin thickness ranging from 0.87 to 2.34 mm (mean, 1.44 mm), which was lower compared to that of the breast model derived from the data of European women. In these previous studies, 4,20,21) the mammographic measurements of small, thin breasts were more affected than those of thicker breasts by the differences between the adipose layers of real breasts and the breast model. In addition, the thickness of skin of a real breast might be lower compared to that of the breast model.…”
Section: Discussionmentioning
confidence: 92%
“…DANCE et al 4) reported that, in younger women, the assumption of the presence of a 5-mm-thick adipose layer is unrealistic for very thin breasts (CBT < 25 mm), and it can lead to estimated glandularities > 100%. JANSEN et al 20) compared breast models composed of different layers, including a model with a 5-mm adipose layer, as proposed by DANCE et al, 4) as well as a two-component model with 3-mm-thick adipose tissue covered by 2-mm-thick skin tissue, at different values of CBT and reported that models with greater breast thicknesses exhibited relatively less attenuation because of increased beam hardening. Additionally, SHI et al 21) reported breast skin thickness ranging from 0.87 to 2.34 mm (mean, 1.44 mm), which was lower compared to that of the breast model derived from the data of European women.…”
Section: Discussionmentioning
confidence: 99%